1968
DOI: 10.3133/cir590
|View full text |Cite
|
Sign up to set email alerts
|

Potential for lode deposits in the Livengood gold placer district, east-central Alaska

Abstract: The Livengood gold placer district of east-central Alaska contains small bedrock deposits that probably were the source of the placer gold. Stream sediments in parts of the district, particularly in the Ruth Creek drainage, are characterized by abnormally high concentrations of gold, arsenic, mercury, antimony, molybdenum, and silver, and Ruth Creek itself is characterized by highly acid water. The area is complex geologically and is cut by many thrust faults, some of which have been invaded by serpentinite. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Present USBM studies have identified monazite and zirkelite in drill core samples (Johnson and McDonald, no date). Subvolcanic rhyolite porphyry stocks like those near Livengood can contain elevated REE and niobium values (Foster 1968). Uranium-bearing vein deposits in the Old Crow batholith, in the Kanuti area, and near Kook Lake on Chichagof Island contain 0.2% to 0.5% REE, nearly all as the cerium subgroup.…”
Section: Silica-rich Depositsmentioning
confidence: 99%
“…Present USBM studies have identified monazite and zirkelite in drill core samples (Johnson and McDonald, no date). Subvolcanic rhyolite porphyry stocks like those near Livengood can contain elevated REE and niobium values (Foster 1968). Uranium-bearing vein deposits in the Old Crow batholith, in the Kanuti area, and near Kook Lake on Chichagof Island contain 0.2% to 0.5% REE, nearly all as the cerium subgroup.…”
Section: Silica-rich Depositsmentioning
confidence: 99%
“…Because the contact between the serpentlnlte, mafic, ultramaflc, and other rocks cannot be seen, 1t 1s not known 1f the Igneous rocks were Intruded or technically emp laced 1n the layered sequences (Weber and others,19B5). The serpentlnltes are believed to have been emplaced originally as subhorlzontal sheets associated with regional thrust faults and their present outcrop pattern reflects subsequent upward dragging along high-angle reverse faults (Foster, 1968). The Paleozoic clastic, serpentlnlte, mafic, and ultramaflc units exhibit a possible structural contact (reverse or thrust faults) with the carbonate-chert unit to the north 1n the Tolovana mining district area (Allegro.…”
Section: Structurementioning
confidence: 99%
“…Some epidote within quartz veins and sericite selvages on quartz veins also occur in this zone. Foster (1968) described the mineralization at the Old Smoky prospect as "narrow, northwestward-trending auriferous arsenopyrite-quartz veins" with samples from the veins containing 3 to 13 ppm gold. The prospect was also considered to be an antimony prospect at one time.…”
Section: Roof Pendantmentioning
confidence: 99%